A companion to Greek lyric - Swift, Laura (Blackwell companions to the ancient world, 2022)
Contexts. The lyric chorus / Lucia Athanassaki -- Religion and ritual in early Greek lyric / William Furley -- Epic and lyric / Adrian Kelly -- Commemorating the athlete / Nigel Nicholson -- Aristocracy, aristocratic culture and the symposium / Marek Węcowski -- Politics / Jonathan M. Hall -- Methodologies and techniques. Papyrology / C. Michael Sampson -- Citation and transmission / Tom Phillips -- Metre and music / Armand D'Angour -- The lyric dialects / Mark de Kreij -- Deixis and world building / Evert van Emde Boas -- Lyric space : Sappho and Aphrodite's sanctuary / Annette Giesecke -- Sappho, performance, and acting fragments / Jane Montgomery Griffiths -- Authors and forms. Iambos / Klaus Lennartz -- Elegy / Krystyna Bartol -- Stesichorus / P. J. Finglass -- Alcman / Timothy Power -- Sappho / André Lardinois -- Alcaeus / Henry Spelman -- Ibycus and Anacreon / Ettore Cingano -- Solon and Theognis / Ewen Bowie -- Simonides / Richard Rawles -- Pindar / Christopher Brown -- Bacchylides / David Fearn -- The new music / Pauline LeVen -- Dramatic lyric / Laura Swift -- The lyres of Orpheus : the transformations of lyric in the Hellenistic period / A. D. Morrison -- Receptions. Greek iambic and lyric in Horace / Andreas T. Zanker -- Greek lyric at Rome : before and after Augustan poetry / Tobias Allendorf -- The gift of song : German receptions of Pindar / John T. Hamilton -- 'Anacreon' in America / Patricia Rosenmeyer -- Greek lyric : a view from the north / William Allan -- Sappho and the feminist movement : twentieth and twenty-first centuries / Marguerite Johnson -- Ann Carson's lyric temporalties / Hannah Silverblank -- Greek lyric and Pindar in Brazil / Robert de Brose.